Indonesia Manufactures: Would It be Trade Competition or Complement to China, Japan and Korea under ASEAN Plus Three? - Rokhedi Priyo Santoso (Economic Journal of Emerging Markets, 2008)
Free trade agreement of ASEAN Plus Three will effectively be implemented in 2010. The establishment of the free trade area will facilitate the realization of potential intra-trade as well as increasing competition of Indonesian products especially manufactures which are intensively traded with the Three. This paper is aimed at analysing the potential trade com-petition and trade complement of Indonesia manufactures to China, Japan, and Republic of Korea under that agreement. Manufactures data used are 3 digits SITC 6 between 1996 and 2006, inclusively. For that purpose, this paper employs an export similarity index (ESI) to identify competitive trade relation; and intra-industry trade index (IIT) to determine com-plementary trade relation. The main finding is that Indonesia and China has more competi-tive trade relation for all categories of manufactures. Both countries have greater similarity in their export structures than that of Japan and Republic of Korea. Conversely, Indonesian manufactures industries have higher complementary trade relation with Japan than with China or Republic of Korea. Thus, forming free trade area between ASEAN and the Three would bring potential competition challenge from China as well as opportunity of intra-industry trade expansion especially from Japan. Keywords: Trade Complementary, Trade Competition, Export Similarity Index, Intra Indus-try Index